2010
DOI: 10.1080/09064702.2010.515241
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of body condition and leg weakness in the blue fox (Alopex lagopus)

Abstract: In recent years, the size and fatness of blue foxes have increased because the length of the pelt is an important factor affecting its price. However, extreme fatness poses a risk to the animal's welfare and increased body weight (BW) has been suspected as a predisposing factor for leg weakness (LEG). The main purpose of this study was to estimate the genetic parameters of body condition score (BCS), LEG and ability to move (MOVE) in the blue fox. Heritabilities for BCS, LEG and MOVE were found to be moderate:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…In our study, the estimated heritability for gSI (0.28) was higher than observed by Peura et al (, ) and Koivula et al (), but lower than in a single‐farm study by Kempe et al (). Indeed, there is fairly large variation in the heritability estimates reported for body size, ranging from 0.16 to 0.32 (Kempe et al, ; Koivula et al, ; Peura et al, ). The heritability for gQU was also higher in our study than in the study of Peura et al ().…”
Section: Discussioncontrasting
confidence: 84%
“…In our study, the estimated heritability for gSI (0.28) was higher than observed by Peura et al (, ) and Koivula et al (), but lower than in a single‐farm study by Kempe et al (). Indeed, there is fairly large variation in the heritability estimates reported for body size, ranging from 0.16 to 0.32 (Kempe et al, ; Koivula et al, ; Peura et al, ). The heritability for gQU was also higher in our study than in the study of Peura et al ().…”
Section: Discussioncontrasting
confidence: 84%
“…Because subjective size scoring is affected by the fatness of the animal, in addition to its length and body weight, emphasizing grading size in selection may simultaneously increase average levels of fatness in blue fox production (Kempe et al . ). Owing to antagonistic genetic correlations (Kempe et al .…”
Section: Discussionmentioning
confidence: 97%
“…Kempe et al . (, ) and Kempe & Strandén reported that size traits (animal size, body condition score, pelt size) had several antagonistic genetic and/or phenotypic correlations with eye infection and leg conformation traits. However, we were unable to calculate economic value of leg conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time period was not available in the current study, and is higher than the heritability estimate for RFI on August (105 days of age). In addition, Kempe et al (2010) obtained a heritability of 0.28 for feed efficiency (gain : dry mater intake) for the total period from midAugust to mid-October period in blue fox. The differences between the above studies and the current study could be due to the method of estimating feed efficiency, with RFI explaining the proportion of feed intake that is independent of BW gain compared to feed efficiency as a ratio trait that contains the genetic properties of feed intake and BW gain.…”
Section: Heritabilitiesmentioning
confidence: 99%